Intracardiac foreign body resulting from a transmediastinal gunshot mimics an extracardiac foreign body: An image presentation - Hsun-Yi Fu; Mao Ting; Yi-Chia Wang; Hsi-Yu Yu (Journal of the Formosan Medical Association, 2017)
A transmediastinal gunshot wound (TMGW) is one of the most severe traumatic injuries, with a high mortality rate. Prompt diagnosis and emergency surgical intervention with or without cardiopulmonary bypass are usually required to save lives. We report a particular case of TMGW in which the computed tomography imaging findings indicated an extracardiac foreign body. However, intraoperative findings revealed an intracardiac foreign body, and urgent cardiopulmonary bypass was performed to remove the foreign body. We suggest that cardiopulmonary bypass should be on standby during an exploratory sternotomy for TMGW, when the trajectory of the bullet hints at a cardiac-penetrating injury according to imaging studies and the location of the bullet remains unaffected by the patient's postural changes.